Short-term water exercise effects on the physical fitness of elderly subjects from cold snowy region - Hanai, A.; Yamamoto, K.; Hatakeyama, T.; Hareyama, S.; Morita, N.; Okitai, K.; Nomura, T. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of the present study was to investigate the effects of short term water exercise on the physical fitness of elderly subjects from cold snowy region. Balance, reaction time and strength are important elements to prevent slips and falls on the frozen streets during winter season. Eleven subjects of the water exercise group (W-group, mean age: 59.4±9.2yrs) participated in a water exercise class for 6 weeks (twice a week for 90 min session). Eight subjects also served as a controlled group (mean age: 62.1 ±8.5yrs). As a result, systolic blood pressure, sitting trunk flexion and reaction time was significantly improved in W-group despite of the short term water exercise protocol. It was suggested that short term water exercise was beneficial to improve systolic blood pressure, flexibility and reaction time of elderly subjects from cold snowy region.